A Perspective on Research on Dishonesty: Limited External Validity Due to the Lack of Possibility of Self-Selection in Experimental Designs - Houdek, Petr (Frontiers in Psychology, 2017)
The aim of this perspective article is to show that current experimental evidence on factors influencing dishonesty has limited external validity. Most of experimental studies is built on random assignments, in which control/experimental groups of subjects face varied sizes of the expected reward for behaving dishonestly, opportunities for cheating, means of rationalizing dishonest behavior etc., and mean groups’ reactions are observed. The studies have internal validity in assessing the causal influence of these and other factors, but they lack external validity in organizational, market and other environments. If people can opt into or out of diverse real-world environments, an experiment aimed at studying factors influencing real-life degree of dishonesty should permit for such an option. The behavior of such self-selected groups of marginal subjects would probably contain a larger level of (non)deception than the behavior of average people. The article warns that there are not many studies that would enable self-selection or sorting of participants into varying environments, and that limits current knowledge of the extent and dynamics of dishonest and fraudulent behavior. The article focuses on suggestions how to improve dishonesty research, especially how to avoid the experimenter demand bias.